2015
DOI: 10.1007/s10646-015-1595-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cd+2 on phosphate solubilizing abilities and hydrogen peroxide production of soil-borne micromycetes isolated from Phragmites australis-rhizosphere

Abstract: The aims of this work were to evaluate the phosphate-solubilization and hydrogen peroxide (H2O2) production by the soil-borne micromycetes, Aspergillus japonicus, Penicillium italicum and Penicillium dipodomyicola, isolated from Phragmites australis rhizosphere and to study the effect of several concentrations of Cadmium (Cd(2+)) on both variables. Our results showed that P. italicum achieved a higher P-solubilization and H2O2 production than A. japonicus and P. dipodomyicola, as only P. italicum showed a posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Some nematophagous fungi, such as Arthrobotrys oligospora and Purpureocillium lilacinum (=Paecilomyces lilacinus), have also shown mineralsolubilizing abilities (Duponnois et al, 2006;Hernandez-Leal et al, 2011). In recent years, several studies have focused on the characterization and evaluation of mineral-solubilizing microorganisms with the aim of incorporating them into sustainable agricultural management strategies (Sharma et al, 2013;Yin et al, 2015;Fu et al, 2016;Zúñiga-Silva et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Some nematophagous fungi, such as Arthrobotrys oligospora and Purpureocillium lilacinum (=Paecilomyces lilacinus), have also shown mineralsolubilizing abilities (Duponnois et al, 2006;Hernandez-Leal et al, 2011). In recent years, several studies have focused on the characterization and evaluation of mineral-solubilizing microorganisms with the aim of incorporating them into sustainable agricultural management strategies (Sharma et al, 2013;Yin et al, 2015;Fu et al, 2016;Zúñiga-Silva et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, microbial P solubilization was also reported to mobilize Cd from soils by increasing the soil acidity ( Chen Y. et al, 2020 ). The microbial P solubilization gene is widely distributed in microbes in Cd-contaminated environments ( Zuniga-Silva et al, 2016 ). In addition, this gene was affiliated with Gemmatimonas and Sphingomonas at the genus level, both of which were enriched in the rhizosphere microbiomes of the AE of S. alfredii .…”
Section: Discussionmentioning
confidence: 99%
“…In another study on native SBM from a Mexican coffee plantation, Hernando-Posada et al (2013) reported that Paecilomyces marquandii and Penicillium janthinelum released 1.9 and 7.0 mg/L of P from Ca 3 (PO 4 ) 2 in the culture medium at 24 days; these values were lower than those achieved by Penicillium SP1 and P. hispanicum. The ability of a fungal strain to release P from an inorganic source is known to be strain and species dependent and can also be influenced by multiple environmental factors (Zúñiga-Silva et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Only Penicillium isolate SP16 was identified at molecular level using the methodology described by Zúñiga-Silva et al (2016). After genomic DNA extraction, PCR amplification of the internal transcribed spacers (ITS regions: 26S and 16S regions) were carried out using the following primers ITS1 (5´-TCCGTAGGTGAACCTGCGG-3´) and ITS4 (5´-TCCTCCGCTTATTGATATGC-3´).…”
Section: Molecular Identificationmentioning
confidence: 99%
See 1 more Smart Citation